High-Pressure EPR and Site-Directed Spin Labeling for Mapping Molecular Flexibility in Proteins - Lerch, Michael T; Yang, Zhongyu; Altenbach, Christian; Hubbell, Wayne L (Methods in enzymology, 2015)
High hydrostatic pressure is a powerful probe of protein conformational flexibility. Pressurization reveals regions of elevated compressibility, and thus flexibility, within individual conformational states, but also shifts conformational equilibria such that "invisible" excited states become accessible for spectroscopic characterization. The central aim of this chapter is to describe recently developed instrumentation and methodologies that enable high-pressure site-directed spin labeling electron paramagnetic resonance (SDSL-EPR) experiments on proteins and to demonstrate the information content of these experiments by highlighting specific recent applications. A brief introduction to the thermodynamics of proteins under pressure is presented first, followed by a discussion of the principles underlying SDSL-EPR detection of pressure effects in proteins, and the suitability of SDSL-EPR for this purpose in terms of timescale and ability to characterize conformational heterogeneity. Instrumentation and practical considerations for variable-pressure continuous wave EPR and pressure-resolved double electron-electron resonance (PR DEER) experiments are reviewed, and finally illustrations of data analysis using recent applications are presented. Although high-pressure SDSL-EPR is in its infancy, the recent applications presented highlight the considerable potential of the method to (1) identify compressible (flexible) regions in a folded protein; (2) determine thermodynamic parameters that relate conformational states in equilibrium; (3) populate and characterize excited states of proteins undetected at atmospheric pressure; (4) reveal the structural heterogeneity of conformational ensembles and provide distance constraints on the global structure of pressure-populated states with PR DEER.